Pengaruh Beban Kerja, Perilaku Individu Dan Disiplin Kerja Terhadap Prestasi Kerja Perawat Pada Rumah Sakit Umum Daerah Aek Kanopan Labuhanbatu Utara - Raja Saul Marto Hendry (LPPM Universitas Labuhanbatu, 2021)
The purpose of this study was to determine the effect of workload, individual behavior and work discipline on employee performance at AEK Kanopan Labuhanbatu Utara Regional General Hospital both partially and simultaneously. The sample in this study amounted to 54 people. The analysis method used is descriptive analysis, multiple Linear regression analysis, T test, F test, and coefficient of determination and the data is processed using the IBM SPSS Statistics 23 program. The results of the hypothesis test showed that partially workload positive and significant effect on employee performance, it is seen from the value of Thitung for workload is thitung 2,2,839.2,730 > ttable 2.00, with a significant value of 0.035 < 0.05. Individual behavior has a positive and significant effect on employee performance, it is seen from the value of thitung for individual behavior is thitung 2.781> ttable 2.730 with a significant value of 0.047 < 0.05. Work discipline has a positive and significant effect on Employee Performance, This can be seen from the value of thitung for work discipline is thitung 2.746 > ttable 2.730, with a significant value of 0.031< 0.05. Ftable value is 2.76, Fcount value is 5.54 >2.76, and significant value is 0.004 < 0.05. This shows that simultaneously The Independent Variable has a positive and significant effect on the Dependent variable.